1999
DOI: 10.1097/00000658-199904000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Cholecystectomy: Risks of the Laparoscopic Approach and Protective Effects of Operative Cholangiography

Abstract: Operative cholangiography has a protective effect for complications of cholecystectomy. Compared with OC, LC carries a nearly twofold higher risk of major bile, vascular, and bowel complications. Further study is required to determine the extent to which potentially preventable factors contribute to this risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
341
5
21

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 481 publications
(379 citation statements)
references
References 28 publications
12
341
5
21
Order By: Relevance
“…Despite variation on opinions about the routine or selective use of IOC, it has demonstrated a reduction in the incidence of major BDI and expeditiously identifies insults at the time of surgery [2,13,52,59,[70][71][72][73]. Archer et al [13] reported that routine use of IOC increased detection of BDI from 45 % to 85 %, which is similar to the increased detection described by Ludwig et al [9] from 45 % to 90 %.…”
Section: Importance Of Intraoperative Detection Of Bdimentioning
confidence: 83%
“…Despite variation on opinions about the routine or selective use of IOC, it has demonstrated a reduction in the incidence of major BDI and expeditiously identifies insults at the time of surgery [2,13,52,59,[70][71][72][73]. Archer et al [13] reported that routine use of IOC increased detection of BDI from 45 % to 85 %, which is similar to the increased detection described by Ludwig et al [9] from 45 % to 90 %.…”
Section: Importance Of Intraoperative Detection Of Bdimentioning
confidence: 83%
“…Laparoscopic cholecystectomy is widely accepted as an effective treatment for benign gallbladder disease, but bile duct injury remains a serious complication, with an incidence of 0.3%–0.7% 1, 2, 3, 4, 5, 6. Bile duct injury is often caused by misinterpretation of the anatomical structures rather than by insufficient technical skills 7.…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic cholecystectomy is recommended in co-incidental biliary pathology including acute cholecystitis episode, obstructive jaundice, previous biliary pancreatitis and history of abdominal surgery. These condition are associated with a higher conversation rate, a prolonged operating time, an increased post operative wound infection and a longer postoperative time [23][24][25][26]. Innumerable anatomic variations of extrahepatic biliary system have been described in the literature.…”
Section: Discussionmentioning
confidence: 99%